ASSESSMENT OF GENETIC DIVERSITY AMONG THE TWELVE CHINESE MEAT GOAT BREEDS USING WEITZMAN APPROACH - Ling Ying-Hui; Wang Li-Sheng; Guo Xiao-Fei; Xiang Hao; Zhang Yun-Hai; Ding Jian-Ping; Zhang Zi-Jun; Zhang Xiao-Rong (Journal of Animal and Plant Sciences, 2014)
The genetic diversity of livestock breeds plays an important role in livestock production, but the significant loss of breeds is threatening genetic diversity of farm animal genetic resources (AnGR). The Weitzman approach which was accepted as a framework for assessment of genetic diversity on AnGR was exploited. In this study, Weitzman method was applied to set the priority of conservation by using genetic parameters of 12 Chinese meat goat breeds. Several measurement indexes of genetic diversity, involving total genetic diversity, contributions of each breed to the total diversity, marginal diversities, conservation potential, were calculated based on 11 microsatellite marker data of 12 Chinese meat goat breeds. The expected diversity of 12 goat breeds was 7132 which was 50.03% of the total genetic diversity. The mean extinction probability of 12 breeds was 0.375, where Hainan black goat was the highest, followed by Tibet goat, Haimen goat and Guizhou white goat. The marginal diversity of Hainan black goat in all breeds was the highest (-0.312), Fuqing goat was the lowest (-0.189). Hainan black goat had the greatest relative contribution to overall genetic diversity, followed by Maguan goat, Yichang white goat and Tibet goat. According to the trend of extinction, the conservation priorities of 12 breeds were Hainan black goat, Tibet goat, Guizhou white goat, Maguan goat, Chengdu ma goat, Haimen goat, Jianchang black goat, Anhui white goat, Fuqing goat, Yichang white goat, Shannan white goat and Matou goat. The Weitzman approach is a new idea to biodiversity resources protection, which is a reference for breed conservation and the decision-making of the relevant policy.  We hope to provide objective and rational criteria and strategy for decision-making in conservation of Chinese meat goat breeds.
Keywords: marginal diversity; conservation priority; goat; conservation potential